Group Analysis - Benner, Erin (Groupwork, 2012)
This paper reflects upon groupwork with patients in a hospital-based eating disorder treatment program. It discusses the importance of reflection and evaluation of our own practice, as well as specific challenges and successes that I encountered while doing groupwork. This paper also relates groupwork theory to my individual work, and outlines key concepts that are central to practicing group therapy.